The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1515/freq.2008.62.7-8.180
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst State Observation via the Perturbation of a Microwave Cavity Resonator

Abstract: The state of the three-way catalyst (TWC) of a gasoline engine is commonly estimated by measuring the air-to-fuel ratio in the exhaust gas. This indirect method suffers from several disadvantages that one could avoid by directly observing the catalyst state and in particular its oxygen loading. We have investigated an RF approach to this direct measurement problem which is based on the fact that the TWC and its stainless steel canning form a filled cavity resonator. It will be shown that the resonator is pertu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 1 publication
0
29
0
1
Order By: Relevance
“…A typical S11-spectrum around a resonance mode is shown in Figure 1b. Further details on the microwave cavity perturbation method applied in the automotive exhaust can be found in [15,18,19]. Prior investigations with this method on the state observation of three-way catalysts with the size of ∅ 4.66″ × 6″ (∅ 11.84 cm × 15.24 cm; full size as it is installed in the exhaust pipe) [11,12,20] and ∅ 1″ × 3″ (∅ 2.54 cm × 7.62 cm; typical lab sample) [6,8] have shown that there is a good correlation between the resonance parameter "resonance frequency" and the catalysts' oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…A typical S11-spectrum around a resonance mode is shown in Figure 1b. Further details on the microwave cavity perturbation method applied in the automotive exhaust can be found in [15,18,19]. Prior investigations with this method on the state observation of three-way catalysts with the size of ∅ 4.66″ × 6″ (∅ 11.84 cm × 15.24 cm; full size as it is installed in the exhaust pipe) [11,12,20] and ∅ 1″ × 3″ (∅ 2.54 cm × 7.62 cm; typical lab sample) [6,8] have shown that there is a good correlation between the resonance parameter "resonance frequency" and the catalysts' oxidation states.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 It was even shown that the state of automobile three-way-catalysts under lean and rich synthetic exhaust gas, respectively, can be monitored qualitatively by using the catalyst housing as microwave resonator and determining its resonance characteristics in situ. 20,21 However, to the best of our knowledge MCPT has not been used to quantitatively determine the complex permittivity and conductivity of catalysts under working conditions, i.e. in a reactor at elevated temperatures in a reaction gas mixture while monitoring the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of the measurement technique can be found in the literature (Fischerauer et al, 2008(Fischerauer et al, , 2010a. Microwave concepts such as electromagnetic waveguides, cavity resonators, and S-parameters are treated in many standard texts (Harrington, 1961).…”
Section: Principlementioning
confidence: 99%